A New Financial System for Poverty Reduction and Growth - Bossone, Biaggio (IMF Working Papers; Working Paper, 2002)
Our proposal draws on the premise that the availability of stable demand deposits for bank lending, in the process of which inside money is created, does not require any act of intentional saving. The mechanism allowing banks to lend deposits does not function well in low-income countries, owing to a number of structural constraints. We argue that separating inside money creation from lending, and distributing it on a nonlending basis to depositors through specialized payment service institutions, could broaden access to financial resources, fuel non-inflationary, demand-led growth; and foster financial deepening, diversification, and stability. We also argue that the proposed reform is consistent with market incentives and sound economic management.